Multi-Strain Tropical Bacillus spp. as a Potential Probiotic Biocontrol Agent for Large-Scale Enhancement of Mariculture Water Quality - Ren, Wei; Wu, Haiwu; Guo, Cong; Xue, Bingqing; Long, Hao; Zhang, Xiang; Cai, Xiaoni; Huang, Aiyou; Xie, Zhenyu (Frontiers in Microbiology, 2021)
Aquaculture is suffering from long-term water eutrophication in intensive-model, whereas the knowledge of multi-strain/specie for improving water quality is extremely limited. Herein, we aimed to develop multi-strain tropical Bacillus spp. as a potential probiotic biocontrol agent for large-scaled enhancement of mariculture water quality. Given the practical application, the optimum multi-strain tropical Bacillus spp. (B. flexus QG-3, B. flexus NS-4 and B. licheniformis XCG-6 with the proportion 5: 5: 4) as a probiotic biocontrol agent was screened and obtained, which effectively improved water quality by removing chemical oxygen demand (COD), ammonia-nitrogen and nitrate, and as well significantly inhibited Vibrio spp. even at relatively low bacterial concentration (104 CFU/mL) in artificial feed wastewater and large-scaled shrimp aquaculture ponds. More importantly, we found that the initial proportion of these three Bacillus sp. strains of multi-strain tropical Bacillus spp. markedly affected the final purification effects, whereas the initial concentration of that only influenced the purification rates at early stage (0-48 h) instead of final purification effects. We reason that this multi-strain tropical Bacillus spp. as a good probiotic biocontrol agent could perform multiple actions, such as COD-degrading, nitrifying, denitrifying and antagonistic actions, for large-scaled enhancement of tropical aquaculture water. Additionally, the multi-strain tropical Bacillus spp. was safe for shrimp and could be stored for at least 240 days in spore form at room temperature. This multi-strain probiotic biocontrol agent may facilitate its adoption for further marine recirculating aquaculture system development and large-scaled commercial application.